The Dynamics of Inter-Regional Collaboration - An Analysis of Co-Patenting - Sidonia von Proff; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2011)
The paper at hand investigates how co-patenting over distance develops when aggregating inventive activities on a regional level. That means, the object of analysis is a link between two regions in contrast to other studies, where links between two individuals or firms are investigated. We analyse which regional characteristics influence the creation and continuation of such links. The main focus lies on different types of distance. The approach adds a dynamic view to the existing, often static literature about collaboration behaviour. The regressions are done for all patent-relevant industries in Germany. We find that several distance types decrease - as expected - the likelihood of link creation but also - not in all cases expected - of link continuation.
Keywords: R11; O34; L14; 330; patents; research collaboration; collaboration dynamics; inter-regional links; Germany